Synthesis of hollow nanostructured nickel oxide microspheres by ultrasonic spray atomization. (August 2016) - Yudin, Andrey; Shatrova, Nadezda; Khaydarov, Bekzod; Kuznetsov, Denis; Dzidziguri, Ella; Issi, Jean-Paul
Abstract: NiO nanostructured powders were synthesized by an ultrasonic spray pyrolysis (USP) technique. The powders were characterized using low temperature adsorption (BET), X-ray diffraction, scanning electron microscopy (SEM), and a transmission electron microscopy (TEM). The final product of the ultrasonic spray pyrolysis is hollow microspheres with 5–7 μm in diameter. The microspheres are built from nanoparticles with 40–60 nm in diameter. Graphical abstract: Highlights: The ultrasonic spray pyrolysis makes possible the obtaining hollow microspheres. The particles are hollow microspheres with shells built of nanoparticles. The diameter of the spheres is approximately 5–7 µm. The shells are built from nanoparticles approximately 10–30 nm in diameter. Using this powder as initial precursor for obtaining porous filters is reasonable.